Effect of doxorubicin on the histological structure of the kidneys in male albino rats - Al-Hassawi, Wasan W.; Al-Sammak, Maha A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: doxorubicin is one of the most active cytotoxic agents in current use, it has a very potent effect in the treatment of various malignancy either used alone or combined with other cytocidal agents, the antitumor activity of this drug associated with cytotoxic effect such as cardiotoxicity, hepatotoxicity, nephrotoxicity, myelosuppression. Objectives: - this study was designed to investigate the effect of the doxorubicin on the histological structure of the rats’ kidney. Results: - Doxorubicin cause reduction in the body weight and changes in the histological structure of the kidney which are atrophy of some glomeruli with widening of the urinary space between the glomerular tuft and the bowman’s capsule , other glomeruli show expansion of glomerular tuft with obliteration of the urinary space, degenerative changes in the tubular epithelium, increase rate of apoptosis, necrosis, cystic changes of the tubules and vacuolation of the tubular epithelial cells cytoplasm, protein cast formation in the tubular lumen, infiltration of inflammatory cells in the interstitium, proliferation of collagen fibers(fibrosis) in the interstitium and glomerulosclerosis, the follow up animals show persistence and more extensive lesion than group B. Patients and Methods:- one of the most important cytotoxic effect of doxorubicin is nephrotoxicity. Therefor sixteen adult male Wister albino rats have been used in this study, Eight of them were given 1 ml of intraperitoneal injection of normal saline alone daily for six consecutive days and served as a control group (A), The other Eight rats were given intraperitoneal dose of (1mg/kg body weight) doxorubicin, daily for six consecutive days and served as treated group (B), tow animals from group B kept alive without treatment for another week (observation period) as follow up animals to see the reversibility of the renal injury that are caused by doxorubicin. the animals were sacrificed at the end of the experiment, The body weight of the animals were recorded before starting the injection and recorded again just before killing the animals to see the changes in the body weight and the kidney sections were prepared and stained with hematoxylin and eosin stain, Periodic acid Schiff ̓s reagent (PAS), Orcin VanGieson stain, and examined by light microscope. Conclusion: doxorubicin causes marked changes in the normal histological architecture of the rats’ kidney, and these changes are irreversible after cessation of doxorubicin injection (observation period).